ANALISIS PENGENDALIAN PERSEDIAAN CUP 220ML DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA INDUSTRI AMDK DI SUMATERA BARAT - Nurhayana, Nurhayana; Zulhamidi, Zulhamidi (Politeknik ATI Padang, 2020)
One of the bottled water industries in West Sumatra experienced an imbalance between supply and consumer demand, so this became a factor of difficulty in determining the period and quantity of orders for 220ml packaging materials, which resulted in the industry often experiencing shortages. and excess raw materials. So the Economic Order Quantity (EOQ) method will be used to determine the amount of inventory that needs to be ordered at the minimum cost or the optimal level of purchasing 220 ml cup packaging material. According to the company police, the inventory of 220ml cups per order is 2,117,346 pcs and the frequency of purchasing 220ml cups in a year is 24 times, while using the EOQ method, the inventory of 220ml cups per order is 3,969,012 pcs and the frequency of purchasing 220ml. cup in a year is 13 times. An additional suggestion after carrying out the investigation and finding out the inventory problem is for the industry to apply the Economic Order Quantity (EOQ) method in controlling the inventory of 220 ml cups because it can save costs related to inventory. The industry also needs to take into account the amount of safety stock and the original order point to avoid the risk of running out or excess raw materials. This is so that the company will continue to produce if the raw materials ordered take a long time to reach the factory.